High Frequency Performance of Piezoelectric Diaphragms for Impedance-Based SHM Applications † - Rezende, Guilherme [UNESP]; Baptista, Fabricio [UNESP] (My University, 2020)
Piezoelectric transducers are used in a wide variety of applications, including damage detection in structural health monitoring (SHM) applications. Among the various methods for detecting structural damage, the electromechanical impedance (EMI) method is one of the most investigated in recent years. In this method, the transducer is typically excited with low frequency signals up to 500 kHz. However, recent studies have indicated the use of higher frequencies, usually above 1 MHz, for the detection of some types of damage and the monitoring of some structures’ characteristics that are not possible at low frequencies. Therefore, this study investigates the performance of low-cost piezoelectric diaphragms excited with high frequency signals for SHM applications based on the EMI method. Piezoelectric diaphragms have recently been reported in the literature as alternative transducers for the EMI method and, therefore, investigating the performance of these transducers at high frequencies is a relevant subject. Experimental tests were carried out with piezoelectric diaphragms attached to two aluminum bars, obtaining the impedance signatures from diaphragms excited with low and high frequency signals. The analysis was performed using the real part of the impedance signatures and two basic damage indices, one based on the Euclidean norm and the other on the correlation coefficient. The experimental results indicate that piezoelectric diaphragms are usable for the detection of structural damage at high frequencies, although the sensitivity decreases.
Keywords: electromechanical impedance; high frequency; performance; piezoelectric diaphragms; sensitivity; SHM